Police trust-building strategies. A socio-institutional, comparative approach - Schaap, Dorian (Policing and society, 2021)
Police require public trust to do their work well. Recognising this, police organisations across Europe implement various methods to gain trust: trust-building strategies. Surprisingly, the field of trust in the police and police legitimacy has paid scant attention to what the police actually do to improve trust. The present contribution outlines an approach to understanding police trust-building strategies in their social and institutional context applying a comparative, dynamic perspective. Departing from the assumption that trust and legitimacy exist in a dialogue between the public and the police, the author argues that trust-building strategies develop in an unpredictable, dynamic complex of interrelated social and institutional factors. What is seen as a suitable trust-building strategy is determined by dominant ‘rationalised myths’, ways of thinking about what good police work should look like. These are shaped by a diverse range of different actors and factors. This complex affects each phase in the development of police trust-building strategies: problem recognition, generation of strategies, and adoption of strategies. Illustrating the value of the socio-institutional approach towards trust-building strategies, each of these phases is discussed in the context of a comparative, dynamic study of police trust-building strategies in England and Wales, Denmark, and the Netherlands. It is argued that this more sophisticated understanding of trust-building in its social and institutional context does not just tell us something about the police, but also helps us understand how state institutions shape and maintain their position in the complex environments of our changing societies.